2009
DOI: 10.1211/ijpp.17.03.0010
|View full text |Cite
|
Sign up to set email alerts
|

Legal issues in prescription writing: A study of two health institutions in Nigeria

Abstract: The legal implications of non-compliance with WHO standards in prescription writing are discussed, with appropriate recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…None of the prescriptions stated the patient's contact information or weight. In a study from Nigeria, almost all prescriptions were deficient in patient's address but, in contrast to our results, almost all contained the patient's age [20]. In another Sudanese hospital study, the patient's full name was mentioned in 18.8% of prescriptions only [21].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…None of the prescriptions stated the patient's contact information or weight. In a study from Nigeria, almost all prescriptions were deficient in patient's address but, in contrast to our results, almost all contained the patient's age [20]. In another Sudanese hospital study, the patient's full name was mentioned in 18.8% of prescriptions only [21].…”
Section: Discussioncontrasting
confidence: 98%
“…Sawalha et al showed that, in private practice in the West Bank, these details were present on all prescriptions [19]. However, almost all the prescriptions in our study had the prescriber's name and signature; this is consistent with the findings from a study in a teaching hospital in Nigeria where the prescriber's name was mentioned on 80% of prescriptions and the physician's signature was present on 96% [20]. In a study from Sudan, in contrast, the physician's name was mentioned in only 6.7% of prescriptions [21].…”
Section: Discussionsupporting
confidence: 91%
“…Prescribing errors are common among prescribers in Nigeria. [181920] This problem coupled with a low self-awareness of making prescribing errors, prompted our inclusion of interns perception of prescribing errors in the parameters assessed. The questionnaire included a 5-point Likert scale ranging from totally agree to totally disagree to determine respondents’ level of agreement with events that constitute a prescribing error [Appendix].…”
Section: Methodsmentioning
confidence: 99%
“…[1920] In the few studies examining the quality of prescribing by Nigerian medical practitioners, there appears to be a need to improve prescribing quality. However, it is not easy to change the prescribing habits of experienced doctors, thus there is the hope that educating junior doctors to prescribe according to a standard guideline may be a more effective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[234] Writing of prescriptions that lacked appropriate details and other errors were common though may not always result in actual adverse outcomes for patients. [567] However, when prescribers involved in potentially serious prescribing errors were interviewed, most stated that they were not aware of having made any errors in the past. [8] Such a lack of awareness may be because the prescribing, dispensing, monitoring and administration of medicines involve other persons of different professions in the continuum of patient care.…”
Section: Introductionmentioning
confidence: 99%